1969
DOI: 10.1139/v69-702
|View full text |Cite
|
Sign up to set email alerts
|

Anodic behavior of silver in alkaline solutions

Abstract: Data, covering a range of pH and temperature, were obtained for the anodic oxidation of electropolished silver and the results compared with electrodes which had undergone repeated oxidation and reduction cycles. The behavior of the electrode is, in the main, complex, showing, for example, autopotential cycling under certain galvanostatic conditions (-3 pA/cmZ, 25 "C, 0.7 N NaOH), the period of oscillation being about t h. Several other hitherto unreported phenomena were also observed. The main conclusions rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 11 publications
(11 reference statements)
2
21
0
Order By: Relevance
“…5. The intersection of the two lines falls near 0.25 mA cm -2, the current density noted by Dignam et al (5) to be unique. The experimental points in Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…5. The intersection of the two lines falls near 0.25 mA cm -2, the current density noted by Dignam et al (5) to be unique. The experimental points in Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Its growth is terminated rather abruptly with the rapid increase of electrode potential to be followed by the formation of AgO and possibly higher oxides, before oxygen is eventually evolved. It was found that the kinetic behavior of silver electrodes was profoundly influenced by surface conditions (5) and it would thus seem that further studies should be carried out on smooth well-defined surfaces. This paper is concerned primarily with the investigation of the initial electrode process, namely the formation of Ag20.…”
mentioning
confidence: 99%
“…Typical polarization curves for galvanostatic oxidation [18,19,29,30J show a rising potential that peaks and then shows a shallow dip. Figure 5 shows potential measurements corresponding to the optical measurements shown in figure 4.…”
Section: Potential Sweepmentioning
confidence: 99%
“…In the charging situation, the Ag/Ag20 plateau does not persist as long as the Ag20/AgO level, especially at higher current density [24,32,34,35,41,43]. This has led to the conclusion that the layer of AgO is thicker than that of Ag20 [2,3,4,7].…”
Section: Galvanostatic Measurementsmentioning
confidence: 99%